Intellectual Property Rights as The Resource for Creative Economic in Indonesia - Ika Atikah; Ahmad Zaini; Iin Ratna Sumirat (Jurnal Penelitian Hukum De Jure, 2022)
Intellectual Property (IP) objects from copyright such as songs and films have economic value that can improve the country’s economy and can even be used as collateral for credit, but the condition is that they must be registered with the ministry of law and human rights. Law No. 24/2019 has not yet regulated in detail the mechanism for granting credit to creative economy actors with intellectual property collateral objects. The research method used here is in the form of a doctrinal approach to laws and regulations. Primary sources are relevant legal regulations related to intellectual property and credit financing, and secondary sources are books and journals. The purpose of this research is to understand credit financing with collateral in the form of songs and films. PP No.24/2022 provides flexibility for creative economy actors to obtain credit financing not only at bank financial institutions but also at non-bank financial institutions. However, the special conditions that are regulated are that the intellectual property has been registered or registered with the ministry that organizes government affairs in the field of law, the intellectual property has been self-managed, and or the rights have been transferred to another party.